Acción política y social de los pueblos originarios en favor de la configuración del Estado plurinacional comunitario (2021)
This document derives from previous premises to demonstrate how constitutional changes in Bolivia materialized through social and political actions based on the ancestral practices and knowledge of native peoples, giving way to the construction of the Plurinational Community State. Thus, the analysis of the formation of Plurinational States in Latin America seeks to highlight the political and epistemic changes that some countries in the region are currently undergoing. These processes are unknown due to the lack of academic diffusion, which makes people reduce and confuse the term plurinational with others such as multiculturalism, pluriculturalism, or multiethnicity, obscuring the importance of this form of organization. In this sense, clarifying, analyzing, and understanding the political and epistemic positions of Plurinational States, allows us to evidence discourses and practices specific to countries where the presence of ethnic movements and social organizations shows a multiplicity of horizons at different levels, in opposition to the conditioning of the one‑dimensional line of the logic of liberal States, inherited from the European tradition, which exclude through different devices other ways of assuming the political, the human, the ethical, and the scientific.